Evaluation of Patient Satisfaction with Dental Services at Widodo Dental Practice, North Jakarta - Imanuel Bryan Wijaya; Daniela Natasha; Maria Aninggadita Priskawati; Priscilla Olivia (Jurnal Indonesia Sosial Sains, 2026)
Health is an important aspect for every individual because it directly influences lifestyle habits. Clinics play a significant role in improving a person's health. The quality of a clinic is greatly influenced by various factors, one of which is patient satisfaction. A service is considered satisfactory if it can meet the needs and expectations of patients. Therefore, it is important for a clinic to evaluate patient satisfaction with the services provided by doctors, especially at Widodo Dental in North Jakarta. This study involved 210 respondents using a purposive sampling method. Data were collected through a questionnaire using a 5-point Likert scale, and then analyzed using PLS-SEM with the help of SmartPLS 3.0 software. The results showed that doctor services have a significant positive influence on patient satisfaction, with an R-square value of 0.680. Analysis of the measurement and structural models showed that all indicators used in this study were valid and reliable. Doctor services play a very important role in improving patient satisfaction. Clinics are advised to improve communication between doctors and patients so that information provided is clearer and easier to understand. This study contributes to efforts to improve the quality of services in the primary healthcare sector